IMPROVING A BASED SEMICONDUCTOR III-V LASER STRUCTURE EMITTING AT A WAVELENGTH OF 400 nm - Aissat, A.; Chenini, L.; Nacer, S.; Vilcot, J.P. (University of Eloued جامعة الوادي, 2018)
This work focuses on the modeling of a ternary structure based on III-V semiconductor with strained quantum well, InGaN/GaN. We studied the effect of indium concentration (x) on different parameters of the InxGa1-xN/GaN material. Indeed, the incorporation of indium induces a variation of the bandgap energy. Increasing the indium concentration x decreases the bandgap, an important property to obtain the wavelength in the visible region. We also studied the strain effect on the band structure. We have considered the effect of the active zone thickness on the emission wavelength taking into account the effect of the strain ɛ(x) and the indium content x. Then, we modeled the optical gain as a function of the wavelength by varying the well width Lw, the injected electron-carrier density N and x at T = 300K. Finally, we optimized the structure to make a Laser component emitting around 400nm.
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Semiconductors III-V, Nanostructures, Laser, Optoelectronics.